2012
DOI: 10.1038/gt.2012.45
|View full text |Cite
|
Sign up to set email alerts
|

BMP-6 is more efficient in bone formation than BMP-2 when overexpressed in mesenchymal stem cells

Abstract: Bone regeneration achieved using mesenchymal stem cells (MSCs) and nonviral gene therapy holds great promise for patients with fractures seemingly unable to heal. Previously, MSCs overexpressing bone morphogenetic proteins (BMPs) were shown to differentiate into the osteogenic lineage and induce bone formation. In the present study, we evaluated the potential of osteogenic differentiation in porcine adipose tissue- and bone marrow-derived MSCs (ASCs and BMSCs, respectively) in vitro and in vivo when induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 52 publications
(98 reference statements)
4
73
0
Order By: Relevance
“…BMPs are members of the transforming growth factor-β superfamily that are able to induce osteogenic differentiation during embryonic development (11)(12)(13). BMPs exert their biological effects by signaling through two type I serine/threonine kinase receptors, RIA and RIB, which are transduced by Smad1, -4, and -5 transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…BMPs are members of the transforming growth factor-β superfamily that are able to induce osteogenic differentiation during embryonic development (11)(12)(13). BMPs exert their biological effects by signaling through two type I serine/threonine kinase receptors, RIA and RIB, which are transduced by Smad1, -4, and -5 transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…172 However, there is some argument concerning the superior osteogenic potential of genetically modified BMSCs compared to that of modified ASCs both in vitro and in vivo. 174 In another study, Schek et al 146 mixed BMP-7 expressing adenovirus with collagen, fibrin, or cell culture medium and implanted them intramuscularly into nude mice. After 4 weeks, radiological and histological analyses showed a superior ability of fibrin glue to deliver the virus.…”
mentioning
confidence: 99%
“…This may be due to the properties of the seeded cells and the scaffold material. A series of assays have shown that the osteogenic potential of BMSCs is greater than that of ASCs both in vitro and in vivo (Mizrahi et al, 2013). Furthermore, our previous studies show that PGS could induce differentiation of bone marrow mononuclear cells to vascular cells and promote vascular tissue formation by adsorbing plasma proteins and platelets Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%